Long-Term Exposure to Ambient Fine Particulate Matter and Mortality From Renal Failure: A Retrospective Cohort Study in Hong Kong, China. Issue 6 (6th January 2020) - Ran, Jinjun; Yang, Aimin; Sun, Shengzhi; Han, Lefei; Li, Jinhui; Guo, Fang; Zhao, Shi; Yang, Yang; Mason, Tonya G; Chan, King-Pan; Lee, Ruby Siu-Yin; Qiu, Hong; et al.
Abstract: Numerous studies have indicated that ambient particulate matter is closely associated with increased risk of cardiovascular disease, yet the evidence for its association with renal disease remains underrecognized. We aimed to estimate the association between long-term exposure to fine particulate matter, defined as particulate matter with an aerodynamic diameter less than or equal to 2.5 μm (PM2.5 ), and mortality from renal failure (RF) among participants in the Elderly Health Service Cohort in Hong Kong, China, from 1998 to 2010. PM2.5 concentration at the residential address of each participant was estimated based on a satellite-based spatiotemporal model. We used Cox proportional hazards regression to estimate risks of overall RF and cause-specific mortality associated with PM2.5 . After excluding 5, 373 subjects without information on residential address or relevant covariates, we included 61, 447 participants in data analyses. We identified 443 RF deaths during the 10 years of follow-up. For an interquartile-range increase in PM2.5 concentration (3.22 μg/m 3 ), hazard ratios for RF mortality were 1.23 (95% confidence interval: 1.06, 1.43) among all cohort participants and 1.42 (95% confidence interval: 1.16, 1.74) among patients with chronic kidney disease. Long-term exposure to atmospheric PM2.5 might be an important risk factor for RF mortality in the elderly, especially among persons with existing renal diseases.